The Role of Risk Management as an Intervening Variable in the Influence of Project Manager Competence and Internal-External Factors on Project Success in Gresik, Indonesia - Diyah Trisulistyorini; Sutinem; Titin (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2026)
This study aims to analyze the influence of Project Manager Competence, Internal Project Factors, and External Project Factors on Project Success, both directly and indirectly, through Risk Management as a mediating variable. This study employs a quantitative approach using a survey method. Data were collected through questionnaires distributed to respondents involved in project management. Data analysis was conducted using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) to examine the relationships between variables and test the research hypotheses. The results show that Project Manager Competence and Internal Project Factors do not have a significant direct effect on Project Success. However, Project Manager Competence has a positive and significant effect on Risk Management and has an indirect effect on Project Success through Risk Management. Internal Project Factors have no significant effect, either directly or indirectly. Meanwhile, External Project Factors have a positive and significant effect on both Project Success and Risk Management. Furthermore, Risk Management is proven to have a positive and significant effect on Project Success. This study concludes that Risk Management plays a strategic role in enhancing Project Success, both as an independent variable and as a mediating variable in project management